Public Knowledge, Attitudes, and Practices towards Antibiotic Use and Antimicrobial Resistance in Eastern Region of Bosnia and Herzegovina in the COVID-19 Pandemic - Dragana Drakul; Bojan Joksimović; Marija Milić; Milica Radanović; Nikolina Dukić; Nenad Lalović; Desmond Nischolson; Biljana Mijović; Dragana Sokolović (MDPI AG, 2023)
The constant worsening of antimicrobial resistance (AMR) imposes the need for an urgent response. Use of antibiotics (AB), both due to irrational prescribing by doctors and irrational use by patients, is recognized as one of the leading causes of this problem. This study aimed to identify knowledge, attitudes, and practices about AB use and AMR within the general population, stratified by age, gender, and urban/rural areas during the COVID-19 pandemic. This questionnaire-based cross-sectional study was conducted in April 2022 among patients who visited three health centers in the eastern region of Bosnia and Herzegovina. A high frequency of AB use was observed during the COVID-19 pandemic (64.2% of respondents were treated with AB). Age and place of residence have not been shown to be factors associated with AB use practices that pose a risk for AMR. However, female gender (β = 0.063; p = 0.041), better knowledge (β = 0.226; p < 0.001), and positive attitudes (β = 0.170; p < 0.001) about use of AB and towards to AMR proved to be factors associated with better practice by respondents. Women, younger respondents, and respondents from urban areas showed better knowledge, attitudes, and behavior about the use of AB and AMR during the COVID-19 pandemic.